2017
DOI: 10.1136/bmjopen-2016-015722
|View full text |Cite
|
Sign up to set email alerts
|

What impact has the NIHR Academic Clinical Fellowship (ACF) scheme had on clinical academic careers in England over the last 10 years? A retrospective study

Abstract: ObjectivesThe Academic Clinical Fellowship (ACF) was introduced to support the early career clinical and research training of potential future clinical academics in England. The driver for the model was concern about falling numbers of clinical academic trainees. This study examines the impact of the ACF model, over its first 10 years, in developing clinical academic careers by tracking the progression of ACF trainees.DesignRetrospective analysis of National Institute for Health Research (NIHR) ACF career prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 3 publications
1
34
0
Order By: Relevance
“…Hauck et al [14], for example, reported an increase in research awareness, con dence and skills and a desire to use research to inform clinical practice in midwives participating in an Australian graduate internship programme. Clough et al [17] reported that supporting early career clinical and research training through fellowships increased the likelihood of securing externally funded doctoral training awards with many fellowship-holders moving into academic roles. Naidoo et al [15] similarly found in their evaluation of a graduate podiatry internship (which was the forerunner of the 2015 -18 programme), that the programme was valuable to the interns' careers and supported research capacity building in foot and ankle rheumatology.…”
Section: Discussionmentioning
confidence: 99%
“…Hauck et al [14], for example, reported an increase in research awareness, con dence and skills and a desire to use research to inform clinical practice in midwives participating in an Australian graduate internship programme. Clough et al [17] reported that supporting early career clinical and research training through fellowships increased the likelihood of securing externally funded doctoral training awards with many fellowship-holders moving into academic roles. Naidoo et al [15] similarly found in their evaluation of a graduate podiatry internship (which was the forerunner of the 2015 -18 programme), that the programme was valuable to the interns' careers and supported research capacity building in foot and ankle rheumatology.…”
Section: Discussionmentioning
confidence: 99%
“…Hard money denotes funds acquired from grant awarding bodies including medical charities, NHS research and developmental schemes or regional trust funds, whereas soft money describes funds from pharmaceutical companies or from an individual consultant’s personal research funds. Although hard money is regarded as more prestigious, it does attract significant competition, with success rates for National Institute for Health Research (NIHR) doctoral research fellowships being significantly higher in those undertaking academic clinical fellowships (ACFs) compared with non-ACF clinical applicants (28% vs 19%) 7. Similar outcomes in fellowship applications have also been observed from the Wellcome Trust and the Medical Research Council 7.…”
Section: Introductionmentioning
confidence: 86%
“…Although hard money is regarded as more prestigious, it does attract significant competition, with success rates for National Institute for Health Research (NIHR) doctoral research fellowships being significantly higher in those undertaking academic clinical fellowships (ACFs) compared with non-ACF clinical applicants (28% vs 19%) 7. Similar outcomes in fellowship applications have also been observed from the Wellcome Trust and the Medical Research Council 7. These findings provide evidence that funding for non-academic trainees to go OOP and undertake doctoral research degrees is becoming increasingly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for research capacity building are varied and include single (individuals or within team / organisation) [4] and multiple (across individuals, organisations and policy levels) strategies [12]. They employ various approaches, including partnerships [1,13], internships [14,15], bursaries [16], fellowships [17], and mentoring [18]. Evaluations of research capacity models have favoured traditional research outputs metrics, such as number of publications or presentations, although other measures have been assessed [4].…”
Section: Introductionmentioning
confidence: 99%